Potensi Pemulihan Pariwisata Halal di Ponorogo (Analisa Strategi Pada Masa Pandemi Covid-19) - Kaukabilla Alya Parangu; Rizqi Rahmawati (Journal of Islamic Economics (JoIE), 2021)
Pandemi Covid-19 mempunyai dampak yang cukup besar pada segala sektor, dan pariwisata halal merupakan sektor yang juga cukup merasakan dampaknya. Penelitian ini menggali potensi upaya pemulihan pariwisata halal dengan pendekatan analisa deskriptif. Menggunakan data terbaru tahun 2020 dan tema yang unik. Metode penelitian menggunakan pendekatan analisa deskriptif, dengan teknik pengumpulan data menggunakan triangulasi berupa observasi, wawancara dan dokumentasi. Berdasarkan penggolahan data diperoleh hasil dari  strategi dengan melakukan Protokol kesehatan berbasis CHSE yaitu Cleanliness (Kebersihan), Health (Kesehatan), Safety (Keamanan), dan Enviroment (Ramah lingkungan) dan juga startegi pemulihan dengan jangka pendek, menengah dan panjang. Strategi jangka pendek lebih mengedepankan dukungan pemerintah daerah, mulai dukungan finansial dan kebijakan yang mendukung. Strategi menengah yaitu dengan menggabungkan peran lembaga pendidikan, pemerintah dan media. Strategi jangka panjang dengan melakukan sistem opersional industri pariwisata, dengan input yaitu memperhatikan kualitas destinasi pariwisata, dan kemudian diprosesnya dengan bantuan penuh pihak pemerintah dan outputnya melakukan pembenahan yang tersturuktur sehingga pariwisata halal di ponorogo dapat perkembang lagi. Dari hasil diatas diperoleh kesimpulan bahwa Pariwisata Halal di Ponorogo telah melakukan pembenahan dengan strategi-setrategi diatas, namun masih belum maksimal sehingga perlu didukung secara penuh oleh Pemerintah daerah, Stakeholder, Media dan Masyarakat.The Covid-19 pandemic has had a considerable impact on all sectors, and halal tourism is a sector that is also quite affected. This study explores the potential of halal tourism recovery efforts with a descriptive analysis approach. Using the latest data for 2020 and a unique theme. The research method uses a descriptive analysis approach, with data collection techniques using triangulation in the form of observation, interviews and documentation. Based on data processing, the results obtained from the strategy by carrying out a CHSE-based health protocol, namely Cleanliness, Health, Safety, and Environment, as well as recovery strategies in the short, medium and long term. The short-term strategy prioritizes local government support, start with financial support and supportive policies. The intermediate strategy is to combine the roles of educational institutions, the government and the media. The long-term strategy is to carry out an operational system for the tourism industry, with input, namely paying attention to the quality of tourism destinations, and then processing it with the full assistance of the government and the output carrying out structured improvements so that halal tourism in Ponorogo can develop again. From the results above, it can be concluded that Halal Tourism in Ponorogo has made improvements with the strategies above, but it is still not optimal so it needs to be fully supported by the local government, stakeholders, media and society. The long-term strategy is to carry out an operational system for the tourism industry, with input that is paying attention to the quality of tourism destinations, and then processing it with the full assistance of the government and the output is making structured improvements so that halal tourism in Ponorogo can develop again. From the results above, it can be concluded that Halal Tourism in Ponorogo has made improvements with the strategies above, but it is still not optimal so it needs to be fully supported by the local government, stakeholders, media and society. The long-term strategy is to carry out an operational system for the tourism industry, with input that is paying attention to the quality of tourism destinations, and then processing it with the full assistance of the government and the output is making structured improvements so that halal tourism in Ponorogo can develop again. From the results above, it can be concluded that Halal Tourism in Ponorogo has made improvements with the strategies above, but it is still not optimal so it needs to be fully supported by the local government, stakeholders, media and society. and then it is processed with the full assistance of the government and the output is structured so that halal tourism in Ponorogo can develop again. From the results above, it can be concluded that Halal Tourism in Ponorogo has made improvements with the strategies above, but it is still not optimal so it needs to be fully supported by the local government, stakeholders, media and society. and then it is processed with the full assistance of the government and the output is structured so that halal tourism in Ponorogo can develop again. From the results above, it can be concluded that Halal Tourism in Ponorogo has made improvements with the strategies above, but it is still not optimal so it needs to be fully supported by the local government, stakeholders, media and society.